DIAGNOSIS OF E.COLI ISOLATED FROM ARTHRITIS IN CHICKENS BY VITEK AND MOLECULAR METHODS - Hameed, S. S.; Ulaiwi, A. H.; Hamad, S. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This study was aimed to identify and confirm of E.coli isolated from arthritis in chickens. Samples for the isolation of the bacteria were taken from broiler chickens with arthritis symptoms (swelling hock joint), and then examined by culturing, VITEK test as well as molecular assay. Antimicrobial susceptibility of bacterial isolate was done. The results showed pink colour colonies on MacConkey agar. The VITEK system was used to identify those colonies. The results revealed that the isolate gave 97 % parallel to those features of E. coli equally recognized by the standard gram negative card. The isolate was found to be sensitive to ticarcillin/clavulanic acid and many others antibiotics and resistance to ticarcillin as well as for other types of antibiotics .The results of the 16Sr RNA gene revealed that E.coli primers of the16S rRNA gene had successfully targeted the respective gene and have shown the single bands of the16S RNA gene at 1500 bp. Sequencing of this gene was performed for the isolate. The results of nucleotide sequencing were submitted in Gene bank database and have accession number: ID: MT012194.1. The phylogenetic analysis Of the isolate was 100% similar to USA:CP048605, Pakistan:GU594300, VitNamHatey: AP022650 and China:MN208222, however, it was 99% similar to India:LCO58573.